Protective Factor Assessments: What Are We Measuring?—An Investigation of the Internal Validity of the Structured Assessment of Protective Factors for Violence Risk - Abbiati, Milena (Criminal justice and behavior, 2020)
The use of instruments measuring protective factors is on the rise in risk evaluation, management, and treatment planning. Although assessment tools must have good internal validity to be generalizable and reproducible, little is known about the internal validity of protective factor instruments. The present study evaluated the factor structure of the Structured Assessment of Protective Factors for Violence Risk (SAPROF) via confirmatory and exploratory factor analyses of forensic risk assessments of 143 individuals convicted of violent and sexual violent offenses in Switzerland. The SAPROF did not show any differences by type of offenses. Although our confirmatory factor analysis did not confirm the classic SAPROF scale’s structure, the results of the exploratory analysis were in line with previous theoretical research as it revealed a four-factor model comprising Resilience, Reintegration, Treatability, and Living Conditions. These results have implications for the use of the SAPROF in forensic risk assessments and treatment management plans.